PELAKSANAAN TANGGUNG JAWAB SOSIAL PERUSAHAAN PADA PERUSAHAAN PEMBIAYAAN KONSUMEN MENURUT PP NO. 47 TAHUN 2012 DI KOTA DENPASAR - Erry Eka Karisma, Gede; Sri Indrawati, A.A.; Dharma Kusuma, A.A. Gde Agung (Kertha Wicara : Journal Ilmu Hukum, 2013)
Injustices in social and economic development created an opening, especiallyin the public access to utilize existing resources. On the other hand, companiesdemonstrate their existence in the world of business, with their ability to utilizeexisting resources in the country. Embodiment of business ethics in the context ofcorporate social responsibility should be accommodated in company policies in orderto achieve company goals, but do not ignore the social community. With a goodrelationship, through CSR activities labeled, will eventually be able to maintain theexistence of the company in the business world. One company whose activities usingnatural resources in the implementation of CSR is a consumer finance company.
Keywords: Social Responsibility, Consumer Finance, Natural Resources, Companies